TMOD-28. NEW APPROACHES FOR ELUCIDATING MEDULLOBLASTOMA DEVELOPMENT VIA HINDBRAIN BLASTOCYST COMPLEMENTATION - Schmidt, Christin (Neuro Oncol, 2020)
Understanding the etiology of brain cancers requires elucidation of developmental origins, genetic drivers, and the tumor microenvironment. This requires reliable in vivo approaches, which are currently lacking. Current in vivo models for pediatric brain tumors rely on generation of xenografts or allografts in immunodeficient mice or generation of transgenic mice. These approaches have severe limitations, including lack of a functional immune system, a restricted developmental time window defined by the cell of origin, or time-consuming workflows for the generation of transgenic mice. We recently developed neural blastocyst complementation (NBC), an organogenesis approach for the forebrain. NBC involves injection of donor mouse embryonic stem cells (ESC) into genetically-engineered blastocysts that are programmed to ablate dorsal telencephalic progenitors. This results in the formation of a donor-cell derived, intact forebrain. Based on this general approach, we are developing an in vivo platform for studies of brain cancer. We will report on our efforts and progress toward the generation of an organogenesis approach for the hindbrain and related studies that aim to define developmental origins and drivers of medulloblastoma.